The Relationship Between Apache Ii Score And Nurses’ Occupational Stress In Icu - Jao, Pei-Ying; Liu, Noreena Yi-Chin; Wu, Hsiu-Lan; Chou, Cheng-Hui; Lin, Kuan-Chia (European Scientific Journal, ESJ, 2021)
Occupational stress remains one of the major concerns among nurses working in ICU, which affects the individuals as well as the quality of patient care. This paper focuses on investigating the correlation between the ICU patient severity and the nurses’ occupational stress. The paper also identifies a number of occupational stress factors. A total of 81 ICU nurses from the teaching hospitals in Eastern Taiwan have been selected to take part in this study through purposive sampling. Cross-sectional study was adopted for this study and interviews were done through a structured questionnaire. The data was collected using the APACHE II scale and the Nursing Stress scale. The result of the correlation analysis between disease severity and occupational stress was found to be insignificant (p > .05). The regression model analysis shows that patient severity plays a moderation effect between nurses’ characteristics and occupational stress. The results of this study could serve as reference to policymakers and nursing administrators to create a supportive environment. Policy changes to improve the nurses’ working conditions were also proposed in this paper.